Il tracollo culturale dell’Ellenismo: una lezione per il presente e un’allerta per il futuro della scienza - MediaGEO, Redazione (Archeomatica, 2024)
In this interview with Archeomatica, Lucio Russo, a physicist, mathematician, and historian of science, delves into a critical turning point in human history: the abrupt collapse of Hellenistic scientific knowledge following the tumultuous Roman conquest of the Mediterranean in the 2nd century BCE. Examining the near-total loss of writings and philosophical-scientific works from that era, the distinguished scholar highlights the challenge of recovering and fully understanding the lost scientific legacy. Throughout the conversation, reflections on potential parallels with the present situation emerge, emphasizing the danger of cultural regression in the age of digital knowledge. A thoughtful exploration that encourages us to carefully scrutinize the past in order to shape clear perspectives on the future of science and culture.